A case of vastus lateralis muscle metastasis of tongue carcinoma - Kitano, Hisataka; Mamiya, Atsushi; Masuda, Yoko; Shinoda, Kenta; Masaoka, Yoh; Suzuki, Michiko (Journal of the Pakistan Medical Association, 2021)
Distant metastasis is the most important prognostic factor for head and neck cancer. This report discusses the case of a 50-year-old man with distant metastasis to the vastus lateralis muscle of tongue carcinoma. The tumorectomy was performed under a diagnosis of tongue carcinoma (cT2N0M0, Stage II). After seven months, radical neck dissection was performed for detected lymph node metastasis in a left supraclavicular lymph node. In addition, metastasis was then detected outside the neck dissection region. Tumorectomy and radiotherapy (50 Gy) were therefore performed. However, left-sided vastus lateralis muscle metastasis was then observed. To the best of knowledge, this is the first report to describe distant metastasis to the vastus lateralis muscle of oral squamous cell carcinoma. Continuous...